2017
DOI: 10.1007/s12264-017-0134-1
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy

Abstract: Ion channels are crucial in the generation and modulation of excitability in the nervous system and have been implicated in human epilepsy. Forty-one epilepsy-associated ion channel genes and their mutations are systematically reviewed. In this paper, we analyzed the genotypes, functional alterations (funotypes), and phenotypes of these mutations. Eleven genes featured loss-of-function mutations and six had gain-of-function mutations. Nine genes displayed diversified funotypes, among which a distinct funotype-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 197 publications
1
101
0
3
Order By: Relevance
“…Functional studies have showed that all KCNT1 mutations led to gain of function, except one that caused loss of function and was identified in a case of severe early infantile epileptic encephalopathy and leukoencephalopathy . Currently, the function alteration of SCN2A mutations identified in epileptic encephalopathies is uncertain . In this study, 4 genes including KCNT1 , SCN2A , KCNQ2 and CLCN4 were identified as putatively causative genes.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Functional studies have showed that all KCNT1 mutations led to gain of function, except one that caused loss of function and was identified in a case of severe early infantile epileptic encephalopathy and leukoencephalopathy . Currently, the function alteration of SCN2A mutations identified in epileptic encephalopathies is uncertain . In this study, 4 genes including KCNT1 , SCN2A , KCNQ2 and CLCN4 were identified as putatively causative genes.…”
Section: Discussionmentioning
confidence: 76%
“…35 Currently, the function alteration of SCN2A mutations identified in epileptic encephalopathies is uncertain. 34 In this study, 4 genes including KCNT1, SCN2A, KCNQ2 and CLCN4 were identified as putatively causative genes. Mutations of KCNQ2 and CLCN4 were not heretofore reported in patients with EIMFS.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recent advances in DNA‐sequencing methods have highlighted the important role of gene‐encoding ion channels in the pathogenesis of DEEs (Wang et al, ). Ion channels are crucial in the generation and modulation of excitability in the nervous system (Wei et al, ). “Channelopathies” are associated with a wide phenotypic and genotypic spectrum as one gene is often associated with different phenotypes and variants in several genes might result in the same epilepsy phenotype (McTague, Howell, Cross, Kurian, & Scheffer, ; Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The potassium channel dysfunctions involved in the other PME phenotypes have been demonstrated by studies aimed at characterising mutated KCNC1 and KTCD7. 4 It can be assumed that the c.890 G > A mutation in the KCNA2 channel (a member of the delayed rectifier class of potassium channels) leads to a gain of function by greatly increasing the potassium current and shifting its activation to more hyperpolarised potentials. The effect of the increased neuronal excitability is currently unclear, [4] but it may involve complex local mechanisms or circuitry rearrangements such as those leading to changes in channel inactivation at nearly resting potentials in excitatory neurons or a decrease in the excitability of inhibitory neurons.…”
Section: Discussionmentioning
confidence: 99%